INTERPRETASI AL-QUR’AN–HADIS TERHADAP MUNCULNYA GERAKAN KAUM JIHADIS - Egi Sukma Baihaki (Farabi, 2017)
Al-Qur'an and Hadith as a guidance of Muslims was interpreted by Muslims with a various perspectives. However, the rise of radical action in religion wich of carry the name of Islam as a "mount" make Islam suspected and discredited by the International public. Jihadisoften use religious arguments from the Qur'an and the Hadith of the Prophet, as a legitimation to their actions including efforts to invite people to follow in their footsteps. This paper will explain how the interpretation of the Qur'an - Hadith among Muslims, especially the concept of jihad which raises the jihadis movement and how the meaning of jihad in Islam itself. Here the authors conclude that jihad is not only meaningful war, but to work and fight for the good conscientious. This meaning has long existed, but ditertutupi by the actions of the Jihadists.